An integrated chemical environment with tools for chemical safety testing. (September 2020) - Bell, Shannon; Abedini, Jaleh; Ceger, Patricia; Chang, Xiaoqing; Cook, Bethany; Karmaus, Agnes L.; Lea, Isabel; Mansouri, Kamel; Phillips, Jason; McAfee, Eric; Rai, Ruhi; Rooney, John; et al.
Abstract: Moving toward species-relevant chemical safety assessments and away from animal testing requires access to reliable data to develop and build confidence in new approaches. The Integrated Chemical Environment (ICE) provides tools and curated data centered around chemical safety assessment. This article describes updates to ICE, including improved accessibility and interpretability of in vitro data via mechanistic target mapping and enhanced interactive tools for in vitro to in vivo extrapolation (IVIVE). Mapping of in vitro assay targets to toxicity endpoints of regulatory importance uses literature-based mode-of-action information and controlled terminology from existing knowledge organization systems to support data interoperability with external resources. The most recent ICE update includes Tox21 high-throughput screening data curated using analytical chemistry data and assay-specific parameters to eliminate potential artifacts or unreliable activity. Also included are physicochemical/ADME parameters for over 800, 000 chemicals predicted by quantitative structure-activity relationship models. These parameters are used by the new ICE IVIVE tool in combination with the U.S. Environmental Protection Agency's httk R package to estimate in vivo exposures corresponding to in vitro bioactivity concentrations from stored or user-defined assay data. These new ICE features allow users to explore the applications of an expanded data space and facilitate building confidence in non-animal approaches. Highlights: ICE provides curated data and tools to support chemical safety testing. In vitro data are mapped to mechanistic targets and regulatory endpoints. Tox21 data are curated using analytical chemistry and assay-specific information. In silico predictions are available for physchem and ADME properties. IVIVE tool uses ICE or user data to estimate in vivo exposure levels.